In vitro investigation of the antiparasitic effects of a pentacyclic triterpene from the toothache plant on intestinal worms of poultry - Pawi Bawitlung Lalthanpuii; Lalrosangpuii; Kholhring Lalchhandama (Open Veterinary Journal)
Background: The management of helminthiasis remains a significant challenge in clinical and veterinary practice because the most important parasites have acquired extensive drug resistance in animal infections and reduced efficacy in human conditions. The toothache plant (Acmella oleracea) is a medicinal plant used in the Mizo traditional system of India for deworming intestinal parasites in both humans and domesticated animals. Therefore, it is important to understand the bioactive components and biological effects of the plant.